Design and characterisation of broadband microstrip reflectarray antennas - Phua, Yeong Nan (2023)
Microstrip reflectarray antennas have the advantages of having a low profile, low loss, and low production cost, making them suitable for high gain and wide bandwidth operation for long-distance communication. However, utilizing the conventional microstrip reflectarray elements such as the rectangular or circular patch elements is difficult to achieve the desired performances. The inherent narrow bandwidth and limited turning ability in such elements have made it difficult to achieve a smooth phase range and broadband reflectarray performance. In this dissertation, three improved designs have been formulated to overcome the mentioned limitations. The first method comprises the usage of a dumbbell-shaped square ring, combined with the Vivaldi tapered slot antenna, which is used to design a broadband reflectarray for the first time. The use of the travelling-wave radiator has enabled the proposed reflectarray element to achieve a full phase range of 371 and a low phase sensitivity of 64.6/mm simultaneously. A 1313 linearly polarized reflectarray is designed and fabricated. Measurement results show an antenna gain of 24.1 dBi with a -1-dB gain bandwidth of 10.6%, and its corresponding aperture efficiency of 40.4% is achievable at the centre frequency of 6.5 GHz. Next, a single-layer circular patch loaded with two unequal slots is designed to enhance the phase tuning ability and achieved a smooth phase range of 458. A low profile 1313 linearly polarized reflectarray is designed and fabricated. Measurement results show that an antenna gain of 23.4 dBi is realizable at the centre frequency of 9.3 GHz with an aperture efficiency of 42%.The -1-dB gain bandwidth of 11.8% has shown much improvement compared to the first design. The third design is a double-layer reflectarray element built using two closely coupled inter-layer ring-patches to improve the phase tuning ability and enhance the broad bandwidth performance. Due to the tight coupling between the inter-layer patches, the coupling between the adjacent reflectarray elements can be significantly minimised. A linear and broad phase range of 527 is achievable, and a 13×13 linearly polarized reflectarray is designed and fabricated. Measurement results show an antenna gain of 23.6 dBi at the centre frequency of 9.3 GHz with an aperture efficiency of 43.8%. The reflectarray features a broad -1-dB gain bandwidth of 33.2%. In conclusion, three unique designs have been demonstrated to overcome the narrow bandwidth of the reflectarray element by improving both the range and linearity of the reflection phase as well as the phase tuning ability. These designs can be employed to design full-fledged reflectarrays and enable wide bandwidth performance.